(untitled) (University of Khartoum Engineering Journal, 2022)
Paper is an important element of our daily life, it is used for writing, printing, cleaning, decoration and packaging. This research is concerned with the importance of paper industry and the relevance of different manufacturing approaches to the daily needs and the available raw materials. The main objective of this research is to investigate the suitability of the Neem (Azadirachtaindica A. Juss) wood for the manufacture of paper and pulp. Samples of the Neem wood were investigated in the laboratory and many tests were made during the manufacturing process to adjust the paper quality produced. Furthermore, several quality tests were carried out on the manufactured paper and compared with recognized standards. It was found that the paper manufactured from Neem wood is of good paper quality and made a good use of a locally available raw material.